The Earth trembled ... then killer waves came! 15 November 1994 Or. Mindoro earthquake. (PHIVOLCS-GDAPD Audio-Visual Unit, 2006)
The video contains a documentation on the earthquake and tsunami that occurred in Oriental Mindoro on November 15, 1994 that caused a great damage in the province.